Genome-wide association study and haplotype analysis reveal novel candidate genes for resistance to powdery mildew in soybean - Liu, Guoqiang; Fang, Yuan; Liu, Xueling; Jiang, Jiacan; Ding, Guangquan; Wang, Yongzhen; Zhao, Xueqian; Xu, Xiaomin; Liu, Mengshi; Wang, Yingxiang; Yang, Cunyi (Frontiers in Plant Science, 2024)
Powdery mildew disease (PMD) is caused by the obligate biotrophic fungus Microsphaera diffusa Cooke & Peck (M. diffusa) and results in significant yield losses in soybean (Glycine max (L.) Merr.) crops. By identifying disease-resistant genes and breeding soybean accessions with enhanced resistance, we can effectively mitigate the detrimental impact of PMD on soybeans. We analyzed PMD resistance in a diversity panel of 315 soybean accessions in two locations over three years. Based on a genome-wide association study (GWAS) approach, we identified a region on chromosome 16 (Chr16) in which 21 genes form a gene cluster that is highly correlated with PMD resistance. In order to validate and refine these findings, we conducted haplotype analysis of 21 candidate genes and indicated there are single nucleotide polymorphisms (SNPs) and insertion-deletions (InDels) variations of Glyma.16G214000, Glyma.16G214200, Glyma.16G215100 and Glyma.16G215300 within the coding and promoter regions that exhibit a strong association with resistance against PMD. Subsequent structural analysis of candidate genes within this cluster revealed that in 315 accessions, the majority of accessions exhibited resistance to PMD when Glyma.16G214300, Glyma.16G214800 and Glyma.16G215000 were complete; however, they demonstrated susceptibility to PMD when these genes were incomplete. Quantitative real-time PCR assays (qRT-PCR) of possible candidate genes showed that 14 candidate genes (Glyma.16G213700, Glyma.16G213800, Glyma.16G213900, Glyma.16G214000, Glyma.16G214200, Glyma.16G214300, Glyma.16G214500, Glyma.16G214585, Glyma.16G214669, Glyma.16G214700, Glyma.16G214800, Glyma.16G215000, Glyma.16G215100 and Glyma.16G215300) were involved in PMD resistance. Finally, we evaluated the PMD resistance of mutant lines from the Williams 82 EMS mutations library, which revealed that mutants of Glyma.16G214000, Glyma.16G214200, Glyma.16G214300, Glyma.16G214800, Glyma.16G215000, Glyma.16G215100 and Glyma.16G215300, exhibited sensitivity to PMD. Combined with the analysis results of GWAS, haplotypes, qRT-PCR and mutants, the genes Glyma.16G214000, Glyma.16G214200, Glyma.16G214300, Glyma.16G214800, Glyma.16G215000, Glyma.16G215100 and Glyma.16G215300 were identified as highly correlated with PMD resistance. The candidate genes identified above are all NLR family genes, and these discoveries deepen our understanding of the molecular basis of PMD resistance in soybeans and will be useful for guiding breeding strategies.